Perspectives of Lithospermum officinale L. Cultivation - Andrushchenko, Olena (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2017)
Lithospermum officinale L. was used by people from ancient times as a magical, religious and medicinal plant. Lithospermum officinale is known for its useful properties as a medicinal and oilseed plant. Now it is of interest as a perspective source of fatty oils, medicinal raw materials, and biologically active compounds. Gromwell in the last century have met as usual in Europe, but researchers of modern flora refer to species that occur sometimes or are offered to regional security lists. In the case of industrial use, there is a need for the introduction of a gromwell into a culture. The features of Lithospermum officinale ontogeny during growing in the Forest-steppe zone of Ukraine are that in the first year of vegetation of plants there are all age states – from sprout to the generative age state, which ends with the formation of a small amount of viable seeds. After the cutting of the aboveground part, there was the formation of proleptic vegetative-generative shoots, on which buds, flowers, and several erems were formed. The formation of sylleptic shoots is characteristic of perennial plants in the second decade of March. When cultivating Lithospermum officinale in the studied conditions it is recommended a sowing before winter, or preliminary stratification of seeds. During spring sowing seedlings were obtained in the second half of May, and sown seeds before the winter – in early April. In laboratory conditions stratified Lithospermum officinale seeds sprouted on the 5th day, germination was 72%. Using of crops is possible in the second year of vegetation. Using of aboveground biomass in the budding phase is due to the high content of biologically active compounds. The content of sugars in the budding phase was 5.4–7.2%, ascorbic acid – 236.3–373.9 mg%, chlorophyll a – 1.39–1.49 mg/g, chlorophyll b – 0.35–0.41 mg/g and carotenoids – 0.77–0.78 mg/g. In culture conditions, the yield of biomass of the gromwell was 1.6 t/ha, and the seeds – 287 kg/ha.